Disseminated varicella-zoster virus infection in an aplastic anemia- paroxysmal nocturnal hemoglobinuria syndrome patient: A case report - Wang, Jie; Yang, Zheng; Ren, Danhong; Shi, Zhanli; Fang, Kun; Li, Zhihui (Frontiers in Cellular and Infection Microbiology, 2023)
Background Varicella-zoster virus (VZV) is a common and widespread human-restricted pathogen. It is famous for its dermatological manifestations, such as varicella and herpes zoster. Patients with aplastic anemia-paroxysmal nocturnal hemoglobinuria (AA-PNH) syndrome complicated with fatal disseminated varicella zoster virus infection are very rare and in danger. Patient concerns A 26-year-old man with a history of AA-PNH syndrome was receiving cyclosporine and corticosteroid treatment in the hematology department. During his hospitalization in our hospital, he developed fever, abdominal pain, and lower back pain, and his face, penis, trunk, and limbs developed itchy rash. Subsequently, the patient had to undergo cardiopulmonary resuscitation because of sudden cardiac arrest, and be transferred to ICU for treatment. It was presumed that the cause is unknown severe sepsis. The patient’s condition quickly progressed to multiple organ failure, accompanied by liver, respiratory, and circulatory failure, and signs of disseminated intravascular coagulation. Unfortunately, the patient died after 8 h of active treatment. Finally, we collected all the evidence and concluded that the patient died of AA-PNH syndrome combined with poxzoster virus. Conclusion AA-PNH syndrome patients treated with steroids and immunosuppressants are prone to various infections, considering that herpes virus infection with chickenpox and rash as the initial manifestations is characterized by rapid progress and often accompanied by serious complications. It is more difficult to distinguish it from AA-PNH syndrome with skin bleeding points. If it is not identified in time, it may delay the treatment opportunity, make the condition worse, and cause serious adverse prognosis. Therefore, clinicians need to pay attention to it.